2001
DOI: 10.1259/bjr.74.877.740048
|View full text |Cite
|
Sign up to set email alerts
|

Skin dose and dose–area product values for interventional cardiology procedures

Abstract: Coronary angiography and percutaneous transluminal coronary angioplasty procedures performed in four different facilities were monitored in the present study by measuring maximum skin dose, dose-area product and other operational parameters. Radiographic slow film, thermoluminescent dosemeters and transmission ion chambers were used to measure dose related quantities. Values of 107-711 mGy for maximum skin dose and 27.3-370.6 Gy cm2 for dose-area product were found, together with cumulative skin dose estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(66 citation statements)
references
References 29 publications
4
62
0
Order By: Relevance
“…The average DAP of 158.2 Gycm 2 found in this study is within the range reported in the literature (28.5-370.6 Gycm 2 ) [24,[36][37][38][39][40][41], but higher than the reference dose level of 75 Gycm 2 established by the European Cardiology research programme DIMOND [37]. A 300 Gycm 2 threshold has also been set for probable induction of skin injury by the European DIMOND research programme.…”
Section: Discussionsupporting
confidence: 82%
“…The average DAP of 158.2 Gycm 2 found in this study is within the range reported in the literature (28.5-370.6 Gycm 2 ) [24,[36][37][38][39][40][41], but higher than the reference dose level of 75 Gycm 2 established by the European Cardiology research programme DIMOND [37]. A 300 Gycm 2 threshold has also been set for probable induction of skin injury by the European DIMOND research programme.…”
Section: Discussionsupporting
confidence: 82%
“…Some authors claim that the DAP is not a suitable quantity for such a monitoring task because of the weak correlation between the DAP and the entrance surface dose [29], and that the latter should be measured directly on the patient. But in the absence of a direct measurement, conversion factors published in the literature [19,[30][31][32][33] may be used to establish the maximum (peak) skin dose from the DAP.…”
Section: Introductionmentioning
confidence: 99%
“…As the DAP does not depend on the patient-to-focus distance, it can be readily measured through a transmission chamber placed at the tube housing level that fully intercepts the incident primary X-ray beam. However, although DAP meters are almost routinely available on radiographic equipment, some authors demonstrated that the DAP value is not an accurate predictor of MSD and deterministic risks [16][17][18][19][20]. It is, however, a relevant indicator to estimate stochastic risks [1].…”
mentioning
confidence: 99%